Preserving Freshness: A Dive into Types and Level of Jujube Fruit Preservatives in Samarahan, Sarawak - Lim, Siong Hee; Sam Froze, Jiee; Kueh, Tze Siew (Global Open Access Journal of Science, 2026)
Introduction: Jujube, also known as Chinese date, is a small, sweet fruit that grows on the Ziziphus jujuba tree. It’s native to southern Asia but has been cultivated in many other regions around the world. The fruit is typically round or oval and can vary in size from a cherry to a plum. Jujubes can be eaten fresh, dried, or preserved and are often used in cooking, baking, and traditional medicine. They’re rich in vitamins, minerals, and antioxidants, making them a nutritious snack option. Various food preservatives, including sulfur dioxide, are applied to jujubes before they are exported from their country of origin. Overdosing or overconsuming sulfur dioxide may cause severe adverse health effects, including cardiovascular and respiratory problems. Thus, this project is aimed to determine the type as well as level of preservative used in jujube that sold at Samarahan district, Sarawak. Methods: Two samples of jujube fruits were obtained from the two largest jujube sellers in Samarahan district in January 2024. The samples were processed directly at the designated food laboratory for analysis of food preservatives, including formaldehyde, benzoic acid, sorbic acid, and sulfur dioxide. Results: Sulfur dioxide was the only preservative identified in both samples, with a reading of 8 mg/kg. No formaldehyde, benzoic acid, or sorbic acid was detected in either sample. Conclusion: The present study indicates that jujube fruits sold in Samarahan district contain normal levels of food preservatives, with sulfur dioxide being the primary preservative utilized for jujube fruit.